REVITALISASI KOMPETENSI PROFESIONALISME PENDIDIK DI DALAM PENDIDIKAN AGAMA ISLAM - Muchamad Agus Munir (EL-TARBAWI, 2018)
This research tries to reformulate the meaning rather than education professionalism in Islamic religious education. The problem that has arisen lately is that educators are only limited to teaching and teaching knowledge to students, and only aborting obligations as teaching professional workers, so it cannot be denied, the quality of educators in PAI is very low in professionalism. Whereas in the PAI the meaning of educators is not only limited to that when viewed in terms of professionalism. There are words of Murabbi, Mu’allim, Muaddib, Mudarris, ahl-Zikr, who have concerns about their individual upbringing patterns. In particular the government has issued a law relating to the professionalism of education personnel, except that in practice many of the educators do not comply with these regulations. The results of this study indicate that Islamic religious education needs to revitalize the professionalism of educators, through the reinterpretation of the concept of educators and combined with government regulations on professionalism. Educators need the creativity of the elements of education, mastery of students, and guidance so that students can develop their potential. Thus the professionalism of educators can be run well. Keywords: Revitalization, Professionalism Competence, Educators, Islamic Education